1976
DOI: 10.1111/j.1365-2141.1976.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective Neutrophil Function in Chronic Granulocytic: Leukaemia

Abstract: The ability of neutrophils to phagocytose, kill and digest Candida guilliermondii was investigated in twelve patients with chronic granulocytic leukaemia (CGL). Following ingestion of organisms there was considerable reduction in the ability of CGL cells to kill Candida and this was not explained by a mild impairment of phagocytosis. Histochemical staining showed that granules containing lysosomal enzymes disappear form the cytoplasm of normal neutrophils during killing and digestion of the fungus, while in CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 25 publications
1
27
0
1
Order By: Relevance
“…In CML, irregular maturation has been described, with the accu mulation of a PMN population which is morphologically relatively mature but functionally immature [22], Some authors have reported a slight reduction in phagocytosis, while the ability to kill microorganisms is severely re duced [6], but occasional reports have described normal phagocytosis [23]. Defective secondary granules and su peroxide production in response to phagocytosis of op sonized particles, as well as the failure of primary granules to fuse with the phagocytic vacuole, have been described [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CML, irregular maturation has been described, with the accu mulation of a PMN population which is morphologically relatively mature but functionally immature [22], Some authors have reported a slight reduction in phagocytosis, while the ability to kill microorganisms is severely re duced [6], but occasional reports have described normal phagocytosis [23]. Defective secondary granules and su peroxide production in response to phagocytosis of op sonized particles, as well as the failure of primary granules to fuse with the phagocytic vacuole, have been described [22].…”
Section: Discussionmentioning
confidence: 99%
“…The transformed stem cell can also simultaneously differ entiate along a single or more than one cell line (clone). Data on PMN function in these disorders are heteroge neous: defects in phagocytosis and bacteria killing have been reported in the literature [6], A second group of clonal proliferative disorders are the myelodysplastic syndromes (MDSs), classified according to the French-American-British guidelines (FAB) as re fractory anemia (RA), RA with excess blasts (RAEB), RAEB in transformation (RAEB-t), RA with ringed sideroblasts (RARS) and chronic myelomonocytic leukemia (CMML).…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro system used to obtain phagocytos ing neutrophils was based on a technique pre viously established in this laboratory [El-Maallem and Fletcher, 1976]. The yeast, C. guilliermondii, cultured in dextrose broth, was used as the target organism.…”
Section: In Vitro Phagocytosismentioning
confidence: 99%
“…This was adapted from the methods of Lehrer [20] and El-Maalem and Fletcher [10]. The test organisms, Candida guilliermondii were washed twice and suspended to give a concentration of 3X107 candida/ml HBSS-gel.…”
Section: Candidacidal Assaymentioning
confidence: 99%
“…Pancytopenia is a characteristic feature and neutropenia is an important un derlying cause of infection in these patients. In a recent study, the incidence of serious infections was 40% [3], There is accumulat ing evidence to suggest that the microbicidal function of neutrophils in various haematological malignancies may be defective [5,9,10,15] and in a recent study the neutrophils in 2 patients with HCL showed an impaired candidacidal activity in vitro [8]. In view of this finding and the possibility that defective function could have clinical relevance, a group of 10 patients with HCL were studied in more detail.…”
Section: Introductionmentioning
confidence: 99%